2018
DOI: 10.1016/j.bbamcr.2018.04.008
|View full text |Cite
|
Sign up to set email alerts
|

The origin of GSKIP, a multifaceted regulatory factor in the mammalian Wnt pathway

Abstract: GSK3β interacting protein (GSKIP) is a naturally occurring negative regulator of GSK3β and retains both the Protein Kinase A Regulatory subunit binding (PKA-RII) domain and GSK3β interacting domain. Of these two domains, we found that PKA-RII is required for forming a working complex comprising PKA/GSKIP/GSK3β/Drp1 to influence phosphorylation of Drp1 Ser637. In this study, bioinformatics and experimental explorations re-analyzing GSKIP's biofunctions suggest that the evolutionarily conserved Domain of Unknown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 45 publications
4
20
0
Order By: Relevance
“…We recently identified residue L130 of GSKIP as a critical point for binding with GSK3β, and the L130P GSKIP mutant resulted in loss of inhibition of neurite outgrowth in human neuroblastoma SH-SY5Y cells [5]. Further studies have demonstrated that mammalian GSKIP favors dimer instead of monomer because the V41/L45 sites are distal to the L130 residue in the GSKIP monomer formation, thus preventing mutual interactions between PKA RII and the GSK3β binding region, indicating that L130 point mutation is essential for the GSK3β binding function [7,9]. To determine whether GSKIP/GSK-3β/Tau could form an assembly, co-IP assay using GFP–Tau was used to pull down GSK3β, GSKIP, and PKA RII, as shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We recently identified residue L130 of GSKIP as a critical point for binding with GSK3β, and the L130P GSKIP mutant resulted in loss of inhibition of neurite outgrowth in human neuroblastoma SH-SY5Y cells [5]. Further studies have demonstrated that mammalian GSKIP favors dimer instead of monomer because the V41/L45 sites are distal to the L130 residue in the GSKIP monomer formation, thus preventing mutual interactions between PKA RII and the GSK3β binding region, indicating that L130 point mutation is essential for the GSK3β binding function [7,9]. To determine whether GSKIP/GSK-3β/Tau could form an assembly, co-IP assay using GFP–Tau was used to pull down GSK3β, GSKIP, and PKA RII, as shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The latter is known to act synergistically with cAMP/PKA signaling to inhibit GSK3β activity [1,7]. GSKIP that directly interacts with GSK3β and negatively regulates GSK3β signaling is required for negative Wnt signaling regulation via a cytoplasmic destruction complex that targets β-catenin for degradation [5,6,8,9]. GSKIP can compete for GSK3β binding, resulting in control of the β-catenin stabilizing phosphorylation at Ser675 by PKA [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, Rock has been a promising therapeutic target for NSCLC. GSKIP is a glycogen synthase kinase-3 (GSK3) β-interacting protein, which is involved as a negative regulator of GSK3-β in the Wnt signalling pathway 52 . Interestingly, the AURK (A, B and C) network was mostly downregulated in lung adenocarcinoma patients with the Ex19del mutation.…”
Section: Comparative Analysis Of Causal Network Inactivation or Activmentioning
confidence: 99%